Persia, the Land of Shiite Faith: The Migration of Imam Ahl al-Bayt and the Encounter between Two Belief Systems in Persia - Fatemeh Sadat Alavi Aliabadi; Sayed Alireza Vasei (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
This article attempts to trace the fundamental role of early Persian beliefs, Zoroastrians, to the decision of Ahl al-Bayt’s choice to migrate to Persia (Iran). This research is based on the fact that there are many places for pilgrimage to imams in Iran. Specifically, this research investigates the similarity of several concepts in both religions, Zoroaster and Islam, regarding the teaching in the principle of God (Ilahiyyah), the principle of life after death (eschatology), and the principle of justice and morals of the religion embraced before Islam in Persia. Several studies have also reported on the distortions, opposition, and the consequences of encountering the two beliefs for the first time between Persian beliefs and Islamic teachings. This study employs a qualitative method with historical analysis and literature study along with relevant information of the study. This article also uses the theory of migration and identity to see the interconnectedness of religion in the migration context. The results of this study show the factors that the Persians are interested in accepting and understanding the teachings of Islam. Those are: first, the emotional closeness of beliefs and moral values between Muslims and Zoroastrians (Magi); Second, the inclusive nature of Islam; third, the absence of racial, gender, and status discrimination in Islamic teachings. The descendants of imams Ahl al-Bayt of the Prophet Muhammad SAW continued the prophet's preaching and the Imams in expanding the spread of Islamic teachings to various regions. During this expansion process, they found Iran as the most secure, and suitable region to accept the presence and teaching of Islam especially the Shiite sect. Therefore, they decided to migrate to Iran, and until now Iran is known as a Shiite country.